2008
DOI: 10.1524/zkri.2008.0025
|View full text |Cite
|
Sign up to set email alerts
|

Neutron photocrystallography: simulation and experiment

Abstract: Abstract.The investigation of light-induced structural changes by diffractive methods has improved significantly in the last two decades. We present here the case of neutron photocrystallography for which we have built a special experimental setup at the single crystal neutron diffractometer TriCS at the Swiss Spallation Neutron Source SINQ. We illustrate the progress of the method on the example of the structural determination of photoinduced nitrosyl linkage-isomers in Na 2 [Fe(CN) 5 NO]⋅2H 2 O. The in-situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In the static case, i.e. when the light-induced structural change is long-lived and thus suitable for collection of X-ray or neutron datasets, the structure of the ground state and the final relaxed light-induced state can be determined (Pillet et al, 2008;Varret et al, 2008;Schefer et al, 2008;Coppens et al, 2008). However, the atomic positions in the two states need to be sufficiently separate and the population, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the static case, i.e. when the light-induced structural change is long-lived and thus suitable for collection of X-ray or neutron datasets, the structure of the ground state and the final relaxed light-induced state can be determined (Pillet et al, 2008;Varret et al, 2008;Schefer et al, 2008;Coppens et al, 2008). However, the atomic positions in the two states need to be sufficiently separate and the population, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While these assumptions allow the main features to be determined, they obviously lead to an incomplete picture of the photo-induced structural change, since the whole molecule relaxes after an electronic excitation and reconfiguration. Helpful in this context are simulations of the local structural changes as a function of population number in order to find whether the novel structure can be detected with the planned measurement (Schefer et al, 2008). An important tool to further identify and determine lightinduced structural changes is density functional theory (DFT) calculations (Delley et al, 1997;Coppens et al, 2002;Delley, 2008;Ishikawa & Tanaka, 2008;Sizova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, these features are not visible strongly enough to exclude an occupational disorder. The results of measurements obtained by Schefer et al [15] shown that the amplitude of occupational modulation of the NbO 6 octahedrons decrease with increase of the barium concentration in the crystal structure. This indicates that the reason of modulation is the ability to occupy pentagonal tunnels by strontium and barium atoms.…”
Section: Resultsmentioning
confidence: 97%
“…The modulation consists of a wave-like tilting of the octahedra so that the O atoms show the largest displacements. In SBN the amplitudes of the positional modulation increase as a function of the strontium substitution rate x (Schefer et al, 2008). The origin of the displacive modulation of the O atoms seems to lie in a modulation of the occupation of the Me2 site (Schefer et al, 2008;Graetsch, Pandey et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…In the present study, the incommensurate crystal structure of CBN crystals with the highest (CBN24) and the lowest barium content (CBN31) are investigated and compared with congruently melting CBN28 and to SBN mixed crystals (Podlozhenov et al, 2006;Schefer et al, 2008). Unlike CBN31 and CBN28, initially CBN24 merely showed a one-dimensional modulation which reduces the symmetry from tetragonal to orthorhombic (Fig.…”
Section: Introductionmentioning
confidence: 97%